Técnicas de siembra y su influencia en los caracteres morfológicos y rendimiento de Coriandrum sativum L., culantro, en la Región Loreto,2023 - Olimar Panaifo, Jessy Raquel (2024)
The thesis on planting techniques for the cultivation of coriander (Coriandrum sativum L.) was conducted in Zungarococha, Loreto, whose objective was to determine its yield in Kg/ha and some morphological characters. The statistical design was the DBCA, ANOVA and Tukey's test with 3 treatments and 6 replications; The treatments were: T1: Continuous groove; T2: Tacarpo and T3: Flute. The results obtained after 45 days were: In terms of plant height, the broadcast technique was statistically significant with 28 cm; Regarding the number of branches/plant, the jet technique was statistically significant than the other treatments with 6 branches; In terms of the number of leaves/plant, the Tacarpo technique was statistically significant, obtaining 17 leaves; In terms of the number of floors/2.5 m2, the broadcast technique stood out with statistical significance with 1,644 floors, n plant weight per 2.5 m2 also the broadcast technique with 3,480 g and finally in weight/ha, the broadcast technique with 8,352 kg with a productivity of S/27,779.00. In terms of production per unit area, broadcast sowing (T3) was the most outstanding technique in terms of productivity.